Q’eros, peru: the regeneration of cosmological relationships and specific identities through Music - Wissler, Holly (2010)
One of the principal purposes of Q’eros music is to actively regenerate and re-create good relationships with the cosmos and the spirit world they believe in. In this paper, I explore how both the Q’eros’ indigenous songs as well as their newly-adopted music and dance for Peru’s largest pilgrimage, Qoyllurit’i, achieve efficacy of purpose through similar techniques of sound production and aesthetics. Even though the specific musical traits (structure, scale, and instrumentation) of both musical styles are significantly different, I address how Q’eros’ musical production of both types share the same focus and serve the same end-goals, whether the ritual is an intimate one within the community or shared with thousands of other people from the greater region. In addition, the performance of both styles of music serve as specific identity markers for the Q’eros depending on their contextual use and the identity desired at the time. In other words, the Q’eros’ musical choices allow them to shift identities between traditional Q’eros in their home community and misti (mestizo) in Qoyllurit’i.